Software-based parallel GHASH: a contiguous approach - Fujii, Hayato; Rossales, Isabela (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2025: Anais Estendidos do XXV Simpósio Brasileiro de Cibersegurança, 2025)
Galois/Counter Mode (GCM) is a widely adopted block cipher mode of operation. Such degree of adoption has led to optimizations at every level, to the point that dedicated hardware support and specialized CPU instructions were developed, reducing the encryption process’ computational overhead. In this proposal, multiple threads concurrently perform encryption and compute the GHASH function — an essential component of GCM — on disjoint segments of the input message. Upon completion, the intermediate authentication tags derived from each segment are combined into a single final authentication tag. This approach exploits a subtle aspect not explicitly addressed in the original specification, which presents GHASH as a strictly serial algorithm.